Structural and optical properties of ZnO thin films obtained by spray pyrolysis - Kalyani, N.; Ching, Yern Chee; Azizi, N. (Taylor & Francis, 2014)
This work concerns the optical and structural properties of transparent zinc oxide thin films deposited by the spray pyrolysis technique. Spray precursor was prepared using zinc acetate, ethanol and acetic acid. The morphology and structural properties of the zinc oxide thin films were studied using field emission scanning electron microscopy and X-ray diffractometry techniques. The thickness of the films was measured by a surface profiler. The photoluminescence was performed using a He-Cd laser with 325 nm laser line. Transmission spectra of the films were analysed by a Cary 50 ultraviolet-visible spectrophotometer. From X-ray diffractometry measurements, zinc oxide thin films showed hexagonal wurtzite structure with cell parameters a = 0.326 nm and c = 0.522 nm. Photoluminescence spectra exhibit an ultraviolet emission peak centred at 390 nm and broad visible emission peaks centred at 620 and 675 nm. The ultraviolet and visible bands were because of exciton and defect-related recombination, respectively. The zinc oxide films exhibit transmittance values as high as 85-90% in the visible region.